Sistem Informasi Ternak Ayam Broiler Berbasis Web - Suherman Suherman (Teknik Informatika, Universitas Pelita Bangsa, 2021)
Abstract Broiler chickens have become excellent in the poultry business in addition to livestock chickens are first done. The interesting thing about broiler business is the harvest time is quite short. In just 40 days broiler chickens can be harvested. This makes the farmers who have limited capital can more quickly turn the capital and reap the benefits. In addition, marketing of broiler chicken meat is quite easy because of the public interest will be meat this one is big enough. But not a few broiler breeders actually lose money and eventually folded, because of lack of knowledge in the field of broiler chickens. The purpose of breeding is a direction that reflects the will of farmers in raising. In this case, what is the hope of the breeder is that it can provide benefits for the breeders themselves. This process starts from the sterilizing process of the cage, the preparation of the place for Doc, the maintenance of Doc until the adult chicken, the provision of drugs, vitamins and vaccines, thinning process, and the harvest process. Processing Data used for receipt of DOC, Feed, and drugs, and the process of harvesting in chicken livestock business is still manual. Therefore the data processing is very slow and less efficient. Keywords : System, Information, Maintenance, DOC, Aya, Broiler